Expression of recombinant enhanced green fluorescent protein provides insight into foreign gene‐expression differences between Mut+ and MutS strains of Pichia pastoris. Issue 5 (13th June 2019) - Theron, Chrispian W.; Berrios, Julio; Steels, Sébastien; Telek, Samuel; Lecler, Renaud; Rodriguez, Christian; Fickers, Patrick
Abstract: Pichia pastoris is a very popular yeast for recombinant protein production, mainly due to the strong, methanol‐inducible P AOX1 promoter. Methanol induction however poses several drawbacks. One approach to improve processes is to use MutS strains with reduced methanol catabolic ability. Various reports claim that MutS allows higher recombinant protein production levels than Mut+ but scarcely elaborate on reasons for differences. In this study, enhanced green fluorescent protein was used as a P AOX1 ‐driven reporter for the investigation of expression differences between Mut+ and MutS strains. Mut+ exhibited higher responses to methanol, with faster growth (0.07 vs. 0.01 hr −1 ) and higher consumption of methanol (2.25 vs. 1.81 mmol/gDCW .hr) and oxygen (2.2 vs. 0.66 mmol/gDCW .hr) than MutS. Mut+ yielded more biomass than MutS (2.3 vs. 1.3 gDCW /L), and carbon dioxide analysis of bioreactor off‐gas suggested that considerable amounts of methanol were consumed by Mut+ via the dissimilatory pathway. In contrast, it was demonstrated that the MutS population switched to an induced state more rapidly than Mut+. In addition, MutS exhibited 3.4‐fold higher fluorescence levels per cell (77, 509 vs. 23, 783 SFU) indicative of higher recombinant protein production. The findings were verified by similar results obtained during the expression of a lipase. Based on the differences in response to methanol versus recombinant protein production, it was proposed that higher energy availability occurs in MutS for recombinant protein synthesis, contrary to Mut+ that uses the energy to maintain high levels of methanol catabolic pathways and biomass production.